Sistem Keamanan Sepeda Motor dengan Teknologi Biometrik Sidik Jari Menggunakan Sensor Fingerprint R305 - Muhammad Nur Ikhsan; Ibrahim Ibrahim; Reni Rahmadewi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
Motorcycles are commonly and widely used vehicles in Indonesia. This vehicle is highly popular because of several advantages they have. Some advantages motorcycles have, among others, easeness of operation and a slim shape that makes them easier to park. But at the same time, it increases interest in committing crimes of motorcycle theft. Worse, the standard security system which is factory default is easier to break into. In this research, a tool is designed to resolve the problem by making double protection on a motorcycle using a fingerprint sensor. The fingerprint sensor acts as double protection in the motorcycle starting process. The fingerprint sensor is a component widely used these days because of its accuracy. The result of the fingerprint registration test shows the average value of fingerprint registration delay is 7.46 seconds and 8.18 seconds for the two objects. The results of testing the alarm system if the readings do not match 3 times will be locked for one minute. After being locked for one minute, the system will reset again from the beginning. From the results of the fingerprint test as a starter, it is found that 20 trials are able to read fingerprints well with the status of registered and unregistered fingerprints. Then it can be concluded that the accuracy of the fingerprint sensor is 100% accurate. The last test of the four different hand conditions shows almost the same delay value, with the dry hand fingerprint response faster than the others.